Uptake, Distribution, and Transformation of Zerovalent Iron Nanoparticles in the Edible Plant Cucumis sativus - Dwivedi, Amarendra Dhar; Yoon, Hakwon; Singh, Jitendra Pal; Chae, Keun Hwa; Rho, Sang-chul; Hwang, Dong Soo; Chang, Yoon-Seok (American Chemical Society, 2018)
Here, we investigated the fate of nanoscale zerovalent iron (nZVI) on the Cucumis sativus under both hydroponic and soil conditions. Seedlings were exposed to 0, 250, and 1000 mg/L (or mg/kg soil) nZVI during 6-9 weeks of a growth period. Ionic controls were prepared using Fe-EDTA. None of the nZVI treatments affected the plant biomass. On the basis of the total iron contents and the superparamagnetic property of nZVI-exposed roots, there was no evidence of pristine nZVI translocation from the roots to shoots. Electron microscopy revealed that the transformed iron nanoparticles are stored in the root cell membrane and the vacuoles of the leaf parenchymal cells. X-ray absorption spectroscopy identified ferric citrate (41%) and iron (oxyhydr)oxides (59%) as the main transformed products in the roots. The shoot samples indicated a larger proportion of ferric citrate (60%) compared to iron (oxyhydr)oxides (40%). The 1.8-fold higher expression of the CsHA1 gene indicated that the plant-promoted transformation of nZVI was driven by protons released from the root layers. The current data provide a basis for two potential nZVI transformation pathways in Cucumis sativus: (1) interaction with low molecular weight organic acid ligands and (2) dissolution-precipitation of the mineral products.
Keywords: ZERO-VALENT IRON; RAY-ABSORPTION SPECTROSCOPY; ENGINEERED NANOMATERIALS; IMPERATA-CYLINDRICA; CERIA NANOPARTICLES; ZNO NANOPARTICLES; FATE; NZVI; NANO; RHIZOSPHERE